Upaya peningkatan keterampilan menyimak bahasa Jerman kelas XI A SMAK St. Fransiskus Xaverius Ruteng melalui multimedia - Jawa, Saturninus Yuvenso; Sahayu, Wening (Universitas Negeri Yogyakarta, 2025)
This study aims to improve (1) the listening skills and (2) motivation to learn German of students of class XI A SMAK St. Fransiskus Xaverius Ruteng through the use of audiovisual- based multimedia. This classroom action research (PTK) involved 35 learners and was conducted in two cycles from November 4 to December 4, 2024. Each cycle included planning, implementation, observation, and reflection stages with four actions. Data collection was conducted through interviews, questionnaires, observations, field notes, documentation, and learner-learning outcomes tests. The results showed a significant improvement in listening skills, with the average score increasing from 84 in the first cycle to 92 in the second cycle. In addition, learning motivation increased from 40% in pre-action to 64% in the first cycle and 91% in the second cycle. Although there were obstacles, such as the speed of the video and difficulty understanding vocabulary, students showed high enthusiasm. Therefore, this study recommends the development and optimization of multimedia-based learning media to increase students' engagement and understanding in learning German.